Simply Jesus: Kesederhanaan Hidup Yesus Kristus dan Transformasi Gereja Kontemporer - Wennar; Josep Tatang (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2025)
Amid globalization and digitalization, many contemporary churches are shifting from Gospel-centered values toward consumerism and digital image culture. Worship services are often turned into visual and emotional entertainment, neglecting the core substance of faith. This trend raises concerns about spiritual degradation and a crisis of identity within the church as a prophetic community. This study explores the theological meaning of Jesus Christ’s simplicity and its relevance for modern church transformation. Using a library research method and thematic exegesis of biblical texts and recent theological literature, the study finds that Jesus’ simplicity is not merely a moral lifestyle but a theological act of kenosis—a rejection of worldly power, luxury, and status. The theology of simplicity offers a constructive response to the erosion of church values through reflective liturgical renewal, ministry-centered leadership reform, and recalibrated digital strategies that emphasize spiritual depth and social witness. The study recommends that churches intentionally embrace the paradigm of Jesus’ simplicity as a framework for cultivating an authentic, transformative, and contextually relevant spiritual community amid the challenges of the modern era.